Women and Philanthropy: Perspectives from Nepal - Malla, Teg (Digital Repository of Theses, 2025)
Natural disasters such as the 2015 earthquake, recent floods, high cost of migrations, and the COVID-19 pandemic have exposed the fragility of Nepal's social and economic systems, highlighting the critical need for philanthropic interventions to build resilience, support vulnerable communities, and invest in long-term recovery and sustainability. Hence, why it is important for women to play a central role in philanthropy. Women bring unique perspectives, foster inclusive solutions, and often focus on grassroots initiatives that directly impact families and communities. Empowering and supporting women in philanthropy not only strengthens resilience but also ensures that resources are allocated to areas that address systemic inequalities and promote sustainable development in times of crisis. The culture, religion, and patriarchal society in Nepal dictate Nepalese women’s roles. Traditionally, women’s roles entail vast household and farm chores, caring for her parents and siblings as a daughter, serving her husband and parents-in-law, and providing for her children's needs, including education. Despite this, an increasing number of women in Nepal aspire to assume leadership positions and combat the daily obstacles they face. Evidence shows women in Nepal are making significant contributions and impacts within the philanthropic sector, including Bidya Devi Bhandari, Nepal’s first female president; Pasang Lhamu Sherpa, the first Nepalese national heroine to successfully climb Mount Everest; Hima Bista, executive director, Nepal at Womankind Worldwide, who protested against the government’s policy violating women’s rights by stating, ‘My vagina will vote you out’; and Bonita Sharma, co-founder, SOCHAI, named one of the most influential women in the world in 2019 by the British Broadcasting Corporation (BBC). Her nonprofit organisation, a youth-led initiative focused on improving health and nutrition for vulnerable women and people. Their desire to make a difference in their community stems from a deep commitment to fostering positive change, empowering others through leadership and role models, and creating opportunities for growth and equity through philanthropy. Therefore, the objectives of this qualitative research study are not only to highlight their works and achievements but also to contribute to the expanding body of literature on women and philanthropy in Nepal and encourage generations of Nepalese women to take up an active role in caring for our people as a whole through philanthropy. By shedding light on their impact, this research aspires to inspire a cultural shift—one where more women step forward as changemakers, leveraging their resources, networks, and influence to create a more equitable, sustainable and compassionate society. It is a call to action for individuals, institutions, and policymakers to recognise and support the vital role of women in shaping Nepal’s philanthropic landscape.